Compairing categories of Lubin-Tate (ϕL, ΓL) modules - Schneider, Peter; Venjakob, Otmar (Results in mathematics, 2023)
In the Lubin–Tate setting we compare different categories of (ϕL, Γ)-modules over various perfect or imperfect coefficient rings. Moreover, we study their associated Herr-complexes. Finally, we show that a Lubin Tate extension gives rise to a weakly decompleting, but not decompleting tower in the sense of Kedlaya and Liu.
Online veröffentlicht: 9. September 2023
Gesehen am 23.11.2023